CASES IN CIVIL COURTS OF THE REPUBLIC OF UZBEKISTAN ON APPLICATIONS FOR THE CANCELLATION OF ARBITRATION DECISIONS OF ARBITRATION COURTS AND THE ISSUANCE OF AN EXECUTIVE SHEET FOR ITS MANDATORY EXECUTION (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article analyzes the work on applications for the cancellation of arbitration decisions in civil courts of the Republic of Uzbekistan and the issuance of an executive sheet for its mandatory execution through the norms in the existing legislative documents of the Republic of Uzbekistan and the information mentioned in the scientific literature, describes in our country what methods and means these works are regulated. Also, the views of a number of legal scholars are covered, and some of the problems that exist in this system are mentioned in our country.